Using GoPro to create an educational database of open urological procedures for residents - MacDonald, Landan; Ory, Jesse; Rendon, Ricardo A.; Bailly, Gregory; Skinner, Thomas; Cox, Ashley; Langille, Gavin; Bell, David (Canadian Urological Association Journal, 2020)
NA